A critique of overpopulation as a cause of pathologies in African cities: Evidence from building collapse in Ghana. (January 2021) - Godwin Boateng, Festival
Highlights: Building collapses are a common, tragic occurrence in developing countries' cities. The population-heavy approach to urban problems lacks explanatory power when applied to specific urban problems in Africa. Africa's urban challenges are historically-institutionally grounded. The public policies of limiting or stimulating urban agglomeration are ill-suited for solving Africa's urban crises. Abstract: Urban discourses in Africa have long followed the conventional pathological–indeed Malthusian–view that the continent's urban problems are the result of overpopulation. This study examines how this diagnosis holds up against evidence on specific urban problems systematically collected and forensically analyzed. The study assembled detailed empirical data on building collapses in cities in Ghana, via interviews and focus group discussions, from a range of professionals, including building inspectors, planners, architects and researchers in the country and draws on data from various secondary sources. The data was knitted together and interpreted within the political economists' methodology of accident research framework . Based on this analysis, the study found that the population-heavy approach to urban problems in Africa totters badly. Not only is it too focused on problems internal to Africa, but it also overlooks the systemic underdevelopment conditions (i.e. inherited and externally-imposed factors) which interplay with the internal factors created the present socio-political-economic order determining life chances of people in cities in the continent. Africa's urban problems, the study will argue, do not stem from population characteristics, but the prevailing socio-political-economic systems that shape, dictate and structure access and the distribution of resources and exercise of power. The socio-political-economic systems are, however, not natural creations – they are the legacies of colonial and post-colonial national policies and the neoliberal-capitalist programs of international bodies implemented in the continent. The present-day conditions in cities in Africa are, therefore, best understood not in the context of their population characteristics, but the various colonial and post-colonial national policies and programs of international bodies that organized and continue to organize the continent's urban systems for particular purposes.